Intuition and problem solving - Style, Alec (1979)
General practitioners use the hypothetico-deductive method of scientific reasoning to solve problems. In the first few minutes of their consultations physicians form initial hypotheses about their patients' problems. This process has childlike, imaginative qualities based on intuition. It is often outside consciousness and probably based on pattern recognition. It has been neglected from study and analysis because of these `mystical' qualities. Yet it is the key to fast and efficient problem solving. If the process could be understood, its efficiency would be improved. This paper is an attempt to explore the nature of general practitioners' intuition.